Differences in Counting Skills between Classes by Using Mental Calculation and Conceptual Methods - Agustina, Tyupnora; Susongko, Purwo; Munadi, Munadi (Journal of English Language and Education, 2025)
The low numeracy of children also has an influencing factor. Factors that affect a child's numeracy ability include internal factors and external factors. The next problem that arises when learning is the lack of interest and attention of students in mathematics lessons so that students lack mastery of the subject and the impact of students will be difficult to understand mathematics lessons. To overcome this problem, the researcher will conduct an experiment using the plucking method. This research uses a quantitative approach because the data obtained is in the form of numbers and the method of data analysis uses statistical analysis. This type of research is a type of experimental research. The place and time of the research used in this study is SMP Negeri 7 Brebes which consists of 18 study groups. The experiment in this study was carried out in 3 (three) stages, namely the pre-test stage, the treatment stage, and the post-test stage. The data analysis method in this study is divided into two stages, namely the initial stage analysis which is an analysis to investigate the similarities of two groups before being given treatment and the final stage analysis which is an analysis to test hypotheses. Based on the data in the output table of the statistics group, it can be seen that the Mean N-gain percent value for the class is quite effective in improving students' numeracy skills and learning interest in learning mathematics integer calculation operation material. As for the conceptual class, the mean N-gain was obtained, the conceptual method was not effective in increasing students' interest in learning mathematics integer counting operations. With the results of this research, it is hoped that it can be used as a consideration in designing learning and the use of the method of learning on students' numeracy.